Studi analisis kesulitan siswa kelas VII SMPN 5 pasirkuda berdasarkan tahapan kastolan dalam menyelesaikan soal himpunan - Silpiani; Senjayawati, Eka (IKIP Siliwangi, 2023)
This study is a descriptive qualitative research for the purpose of analyzing errors and explaining the types of mistakes made by students when solving problems based on the text format provided. This research was conducted at a tertiary institution in Cianjur, with 10 research subjects in class VII B in the odd semester of the 2022/2023 academic year at SMP Negeri 5 Pasirkuda. The data collection method in this study was in the form of a written test. Based on the data presentation, the student error rate is 1) conceptual error, namely 66.9% with a